Silk Belt between Lion and Dragon: Lyon (France)–China ties - Chi, Yumei (Asia in World Politics: Past, Present, and Future, 2021)
In 1964, diplomatic relations between the Government of Charles de Gaulle of the French Fifth Republic and the People’s Republic of China (PRC) were established at an ambassadorial level. This decision was made in the context of the Cold War and embodied in a French geopolitical strategy. At that time, China (PRC) had been isolated by the majority of the Western Powers, and its diplomatic engagement with France had allowed access to some new industrial products and technologies China had particular need of these as the Soviet Union (USSR) had withdrawn all of its technological investments in China during the Sino-Soviet Split in 1960. Some industrial contracts have been signed between the French and Chinese governments since the mid-1960s. Among these contracts, the contributions of the industrialists of Lyon were the most numerous. Paul Berliet (1918–2012) exhibited Berliet trucks in Beijing in 1965, and this was the origin of the first French technology transfer in China. In 1978, Alain Mérieux (1938–) presented in China human and veterinary vaccines from the Institut Mérieux. It is worth mentioning that these Lyon-China relations had originally been initiated by the silk industrialists of Lyon in the 18th century, and were further developed with the first commercial mission between 1843 and 1846. It was the first time since the 15th century, that missions referring to “New Silk Route” had been operated between Europe and China. Since the 19th century, the Lyon-China ties have also extended to many other industrial and technological fields, as well as to the field of education, with the establishment of the Franco-Chinese Institute of Lyon (Institut Franco-Chinois de Lyon) in 1919 in Lyon. These Lyon-China relations persisted and evolved over the centuries, and covered periods of chaotic relations between France and China, notably The Opium Wars (1839–1842, 1856–1860), the Second World War (1939–1945), the Cold War (1947–1991) and the Sino-Western Diplomatic Crisis in 1989. Despite politically divergent ideologies and situations of conflict (particularly between Western countries and the Chinese world following the Cold War), some exchanges have been maintained between Lyon and China, because of the implementation and continuation of Gaullist policy. The aim of this article is to analyze the impact of Gaullist diplomacy on Franco-Chinese industrial and educational exchanges, and to try to reveal the issues and challenges in relations between Lyon and China, in particular in the current political and economic world situation, if Lion (in the Lyon armories) and Dragon (China) ties are to continue to prosper.